The influence of work environment and work motivation on employee performance - Anggraini, Ninik (Journal of Economics and Business Letters, 2024)
This research aims to determine the influence of the work environment and work motivation on employee performance at PT XYZ Central Jakarta, both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling, and the sample obtained in this study was 75 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research show that the work environment has a significant effect on employee performance. Work motivation has a substantial impact on employee performance. The work environment and work motivation simultaneously significantly affect employee performance. The correlation coefficient value is 0.823, meaning that the independent and dependent variables have an extreme level of relationship.